Landslide Dynamics: ISDR-ICL Landslide Interactive Teaching Tools Volume 2: Testing, Risk Management and Country Practices (Springer International Publishing, 2018)
This interactive book presents comprehensive information on the fundamentals of landslide types and dynamics, while also providing a set of PPT, PDF, and text tools for education and capacity development. It is the second part of a two-volume work created as the core activity of the Sendai Partnerships, the International Consortium of Landslides. The book will be regularly updated and improved over the coming years, based on responses from users and lessons learned during its application.